Disonancias entre el entorno local de los negocios y la cultura corporativa en un país latinoamericano - Berlin, Margalit (1995)
The article analyzes the relationship between the corporate culture of a multinational company headquartered in the United States, which enjoys great prestige worldwide, and the business environment and practices in Venezuela, where it has an operation. The prevailing culture in the corporation is North American and the top managers come from their country of origin. In Venezuela, on the other hand, most of the companies are family-owned, and personal contacts and influences prevail. The research is oriented to the elaboration of a qualitative diagnosis, through rigorous observation and semi-structured interviews. The results revealed that there is resistance on the part of Venezuelan managers to follow the culture of a strict company governed by rules set in a very different economic and political context. The ambiguity between acceptance and low identification with the values of the parent company leads to think of corporate culture as fragmented.